2012 IEEE International Conference on Robotics and Automation 2012
DOI: 10.1109/icra.2012.6225249
|View full text |Cite
|
Sign up to set email alerts
|

Field performance evaluation of new methods for in-situ calibration of attitude and doppler sensors for underwater vehicle navigation

Abstract: We report a comparative performance evaluation, using at-sea field data, of recently reported methods for the problem of in-situ calibration of the alignment rotation matrix between Doppler sonar velocity sensors and inertial navigation sensors arising in the navigation of underwater vehicles. Most previously reported solutions to this alignment calibration problem require the use of absolute navigation fixes of the underwater vehicle, thus requiring additional navigation sensors and/or beacons to be located e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Preliminary results of this study were previously reported in conferences papers (Troni & Whitcomb, , , ; Troni, Kinsey, Yoerger, & Whitcomb, ). The present paper is a complete report of the proposed methods and results under different conditions.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Preliminary results of this study were previously reported in conferences papers (Troni & Whitcomb, , , ; Troni, Kinsey, Yoerger, & Whitcomb, ). The present paper is a complete report of the proposed methods and results under different conditions.…”
Section: Introductionsupporting
confidence: 72%
“…The expected position accuracy of a Doppler navigation system is 1–5 % of the distance traveled for a calibrated system using a low‐cost attitude sensor, e.g., Singh, Eustice, Roman, & Pizarro () and Troni & Whitcomb (, b), and 0.1–0.2 % of the distance traveled for the case of a calibrated system using a high‐end attitude sensor, e.g., Troni, McFarland, Nichols, & Whitcomb (), Troni et al. (), and Troni & Whitcomb (, b). An extensive discussion of underwater vehicle navigation can be found in Troni ().…”
Section: Doppler Navigationmentioning
confidence: 99%
“…These methods require the vehicle to run on the surface so that a GPS signal is available (Joyce, 1989; Tang et al, 2013), or additional navigation beacons to be placed at surveyed sites (Kinsey and Whitcomb, 2006; 2007). Troni et al (2012) and Troni and Whitcomb (2010) proposed an in-situ calibration method using only on board DVL, gyrocompass and depth sensors, but the gyrocompass is unrealistically assumed to provide exact absolute attitude. In fact, precise attitude estimation for gyrocompass is not a solved problem and also needs extensive study (Silson, 2011; Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Kinsey and Whitcomb derive an SO(3) constrained adaptive identifier and apply it to this problem in Kinsey & Whitcomb (). Recently, Troni and Whitcomb have adapted the LS methods to estimate the alignment between DVL and INS (Troni & Whitcomb, , ; Troni, Kinsey, Yoerger, & Whitcomb, ). Their method eliminates the need for external position measurements, effectively making it a strap‐down calibration technique.…”
Section: Application To Underwater Robot Navigationmentioning
confidence: 99%